Assessment of Customer Service Satisfaction in Ride-Hailing Platforms: A Study of Bolt in Dar es Salaam - Makanula, Humphrey Leslie; Koshuma, Julieth (International Journal of Supply Chain and Logistics, 2025)
Purpose: The primary objectives of this research were to evaluate the degree of customer satisfaction with Bolt’s services in Dar es Salaam, identify the key factors influencing satisfaction, uncover the main challenges experienced by customers, and explore potential areas for operational improvement. Methodology: A mixed-methods research design was employed to provide a comprehensive assessment. Quantitative data were collected through structured surveys administered to 256 Bolt customers, focusing on app usability, pricing, safety, and overall satisfaction. Qualitative insights were gathered via semi-structured interviews with 30 drivers and focus group discussions with 14 Bolt employees, supplemented by direct observation of 20 Bolt rides. This triangulated approach ensured the validity and reliability of the findings by capturing diverse perspectives and cross-verifying results. Findings: The findings reveal that a majority of customers are satisfied with Bolt’s services, highlighting strengths such as app usability, driver professionalism, and overall reliability. However, several challenges persist, including frequent app crashes during peak hours, unpredictable pricing, unprofessional driver behavior, delays in ride arrivals, and slow customer support responses. Safety concerns, especially during late-night rides, were also noted. These operational gaps negatively impact customer trust and loyalty, underscoring the need for targeted improvements. Unique Contribution to Theory, Policy and Practice: This study contributes to theory by highlighting key factors like app stability, driver training, and pricing transparency in customer satisfaction for ride-hailing in emerging urban markets. For policy, it offers guidance to regulators and companies on improving driver standards and consumer protections. Practically, it provides Bolt with targeted strategies to enhance user experience, safety, and loyalty, supporting its growth in Dar es Salaam’s competitive ride-hailing sector.